Ultrasound evaluation of the Achilles tendon in Olympic athletes making different uses of the lower limbs - Aiello, C. R. (Medicina dello Sport, 2019)
BACKGROUND: The purpose of the study was to use ultrasound to analyze the Achilles tendons in high-level athletes practicing different Olympic disciplines. We considered measurements of the thickness of the tendons and the structural modifications found during check-up visits the athletes attended in preparation for the 2016 Olympic Games in Rio de Janeiro. METHODS: We examined 143 Olympic athletes of an average age of 25.04 years (range: 17-41 years), divided into five groups based on the sports activity they practiced: group A, canoeing/kayaking; group B, rowing; group C, swimming; group D, water polo; group E, athletics. Each subject underwent an ultrasound evaluation of both Achilles tendons using longitudinal and transverse scans. RESULTS: In agreement with the literature, an analysis of the data allowed the identification of a significant increase (P=0.001) in the thickness of both tendons in group E (athletics) compared to groups B (rowing) and D (swimming); with the data normalized for height, the tendon thicknesses of group E were significantly greater than group C (water polo), as well. A particularly significant increase was found in tendon thickness (P=0.001) when compared to all the groups when the Achilles tendons of group E (athletics) were normalized for body weight. Group E (athletics) was also the group with the highest number of symptomatic subjects and the group that reported the most previous morbid events involving the Achilles tendon in their medical histories. CONCLUSIONS: The ultrasound study of the Achilles tendon indicated that morphology is normal when the thickness of the tender venter is between 4 and 6 mm in the middle third. Values over 6 mm, including in the absence of declared clinical symptomatology, suggested a high probability of a pathological tendon that deserved careful follow-up and an appropriate prevention plan